Kitāb talkhīṣ al-Muḥaṣṣal : fī sharḥ al-Muḥaṣṣal fī ʿilm al-kalām - Ṭūsī, Naṣīr al-Dīn (Miras Maktoob, ISBN: 9789004365452., 2020)
Fakhr al-Dīn Rāzī (d. 606/1210) was a prominent theologian, interpreter of the Qurʾān and philosopher. He was born in Rayy where he studied theology, philosophy and law under different masters, including his father, a preacher. After his studies, he started a wandering life which took him to different cities and courts in Transoxania and Khwārazm. He finally settled in Herat where he spent the rest of his life, a wealthy and respected scholar and author of a number of seminal works. Naṣīr al-Dīn Ṭūsī (d. 672/1274) was an influential philosopher, theologian, mathematician and astronomer, besides being the first director of the famous observatory at Marāghah near Tabriz as well as a man of politics. Author of a large number of scholarly works, his influential commentary on Rāzī's Muḥaṣṣal on philosophical theology is a critical appraisal of a work which Ṭūsī considered much overrated. Facsimile of the oldest known copy, dated 669/1270.